PUBLIC RELATION MANAGEMENT STRATEGY IN IMPROVING THE IMAGE OF ISLAMIC EDUCATIONAL INSTITUTIONS IN THE DIGITAL ERA - Mahmud, Mahmud; Sahidah, Ahmad; Khoir, Muhammad Ilzamul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the public relations management strategies implemented by Islamic educational institutions to improve their image in the digital era. The development of information technology, especially social media and digital platforms, has brought significant changes in the way educational institutions communicate with the public. This research uses a qualitative approach with a descriptive case study method, focusing on the implementation of public relations strategies in an Islamic educational institution. Data was collected through in-depth interviews with the madrasa head, deputy head of the madrasa for public relations, students' parents and alums. The research results show that the use of social media and websites as the main communication channels, quick response to negative issues through transparent clarification, and collaboration with stakeholders through digital technology are the main strategies implemented to improve the image of the institution. Public relations management in Islamic educational institutions also focuses on building close relationships with parents, alums and the community to obtain greater support. Overall, this research finds that digital technology-based public relations management strategies can significantly improve the image of Islamic educational institutions as long as they are carried out with effective communication, transparency and ongoing collaboration.